The Influence of Structural Design on the Electronic Properties of a Frisch Grid Cadmium Zinc Telluride Detector by a Finite Element Method - Zhenzhao Zhang; Yu Li; Meng Cao; Weifan He; Zhen Xu; Jian Huang; Linjun Wang (Crystals)
Cadmium zinc telluride (CZT) detectors have the advantages of high detection efficiency and good energy resolution, which are widely used in the fields of X-ray detection, environmental monitoring and nuclear radiation detection. The Frisch grid structure is used more often in the preparation of detectors because of its good unipolarity and simple structure. In this paper, the effects of changing the gate position, width and relative dielectric constant on the electrical properties of Frisch grid CZT detectors, such as potential, weight potential, electric field distribution and charge collection efficiency, are simulated in detail by the finite element method. From the simulation results, the optimisation of the performance of the Frisch grid detector is mainly based on minimising the distance between the gate and anode within a reasonable interval, increasing the area of the Frisch grid and selecting a material with a high relative permittivity for the fabrication of the Frisch grid. The research work contributes to the development of CZT detectors.